ROLE OF PARTNERSHIP PROGRAM TO INCREASE REVENUE AVERAGE EMPLOYEES AND SKILLS DEVELOPMENT FINANCIAL PARTNERS Patronage (Case Study On Apple Cider Industry Brosem) - Ulum, SE, M.Miftachul; Widijoko, Dra.,MSA.,Ak, Grace (Jurnal Ilmiah Mahasiswa FEB, 2012)
This study aimed to determine the effect of Partnership Program PT. Telkom to the average income of employees and the ability of Apple Cider Brosem in preparing financial statements that either. Partnership Program is one of its Corporate Social Responsibility PT. Telkom granted to SMEs in the form of capital assistance and training to management in order to grow larger again in the future. This study includes a qualitative descriptive research. The data collection techniques used by the writer is a field study, which consisted of interviews, direct observation, review of written documents, and discussions. Moreover, the authors also conducted a study in the library collection. Data were analyzed by descriptive quantitative and qualitative. The results showed that the Partnership gives a major role in the rapid development Brosem Apple Cider. This is indicated by a significant increase in revenue since capital assistance from Partnership Program in the amount of 15% -30% each year from 2005 to 2010. With financial training provided by this program also Apple Cider Brosem increased the ability to prepare financial statements which can be seen from the quality of the financial statements for the better. Keywords: Corporate Social Responsibility, Partnership Program, the average income of employees, financial statements